Cerebral localization of impaired phonological retrieval during rhyme judgment. Issue 5 (19th September 2014) - Pillay, Sara B.; Stengel, Benjamin C.; Humphries, Colin; Book, Diane S.; Binder, Jeffrey R.
<x xml:space="preserve">Abstract</x> Objective Computation of a prearticulatory phonological representation (phonological access, or phonological retrieval) is an essential process in speech production whose neural localization is not clear. This study combined a specific behavioral measure of phonological access and multivariate voxel‐based lesion‐symptom mapping (VLSM) in a series of left hemisphere stroke patients to identify brain regions critical for this process. Methods Phonological access was assessed in 40 chronic ischemic stroke patients using a silent rhyming task to avoid confounds with motor planning and articulation deficits. Additional covariates were incorporated in the VLSM analysis to control for orthographic and working memory demands of the rhyming task, and for age, education, and total lesion volume. The resulting t statistic maps were thresholded at voxelwise p < 0.001 and cluster‐corrected at a familywise error of p < 0.05. Results Phonological access impairment was correlated with damage to a focal region of cortex and white matter caudal to the posterior sylvian fissure, which included the posterior supramarginal gyrus and adjacent anterior angular gyrus, planum temporale, and posterior superior temporal gyrus. No correlation was observed with Broca's area, insula, or sensorimotor cortex. An additional VLSM showed no correlation between damage in this posterior perisylvian region and spoken word comprehension. Interpretation This is the first demonstration of a specific lesion correlate for phonological access impairment. Although this posterior perisylvian region overlaps with some versions of the classical Wernicke area, the present results demonstrate its involvement in prearticulatory phonological production rather than speech perception or lexical–semantic processes. Ann Neurol 2014;76:738–746